Early Childhood Feeding Practices and the Development of Severe Early Childhood Caries (S-ECC): A Prospective Cohort Study in Medan, Indonesia - Andhika Kurnianta Kusuma; Muhammad Ashraf; Yi-Fen Huang; Aprilia Sari; Firman Hadi; Sohyuk Kim (Phlox Institute: Indonesian Medical Research Organization, 2025)
Introduction: Severe early childhood caries (S-ECC) is a significant public health problem, particularly in developing countries like Indonesia. Early childhood feeding practices are recognized as major risk factors, but prospective data from specific regions like Medan, Indonesia, are limited. This study aimed to investigate the association between various feeding practices and the development of S-ECC in a cohort of children in Medan. Methods: A prospective cohort study was conducted involving 450 mother-child dyads recruited from Posyandu (integrated health posts) in Medan, Indonesia. Baseline data on maternal demographics, socioeconomic status, oral health knowledge, and infant feeding practices were collected via questionnaires and interviews. Children were followed up at 6-month intervals for 36 months. Dental examinations were performed by calibrated dentists using the dmft index (decayed, missing, filled teeth) to diagnose S-ECC. Cox proportional hazards regression was used to analyze the association between feeding practices and S-ECC development, adjusting for potential confounders. Results: The incidence of S-ECC at 36 months was 38.2% (n=172). Prolonged bottle feeding (beyond 12 months) (Hazard Ratio [HR] = 2.15; 95% Confidence Interval [CI]: 1.55-2.98; p<0.001), nocturnal bottle feeding with sweetened liquids (HR = 2.85; 95% CI: 2.01-4.03; p<0.001), and frequent consumption of sugary snacks/drinks (≥3 times/day) (HR = 1.92; 95% CI: 1.38-2.67; p<0.001) were significantly associated with an increased risk of S-ECC. Exclusive breastfeeding for the first 6 months showed a protective effect (HR = 0.62; 95% CI: 0.45-0.86; p=0.004), even after adjusting for socioeconomic status and maternal oral health knowledge. Conclusion: This study confirms the significant impact of early childhood feeding practices on S-ECC development in Medan, Indonesia. Prolonged and nocturnal bottle feeding, particularly with sweetened liquids, and frequent consumption of sugary snacks/drinks were key risk factors. Promoting exclusive breastfeeding for the first six months and educating mothers about appropriate feeding practices are crucial for S-ECC prevention in this population.